BODY AND SOCIETY: THE VIGOREXIA AND ITS IMPLICATIONS (Fiep Bulletin - online, 2016)
The aim of this paper was to identify what are the effects of vigorexia on the body, considering the studies that have been developed in national and international literature on this theme. To achieve the goal outlined a qualitative research bibliographic nature. Thus, it was possible to understand that under the influence of the standards set by the media, men and women have dedicated hours practicing physical exercise in an exaggerated way, moreover, one sees still a high recurrence studies indicating increased consumption of anabolic steroids as resources for increased muscle volume in the body.
Keywords: Body; Vigorexia; Anabolic Steroids.